PROBLEMS OF USINGMODERN INTERACTIVE TECHNOLOGIES IN TEACHING THE UZBEK LANGUAGE TO FOREIGNPERSONNEL IN EDUCATIONAL INSTITUTIONS OF THE MIA (International journal of artificial intelligence, 2026)
The article analyzes current problems of using modern interactive technologies in teaching the Uzbek language to foreign personnel in educational institutions of the Ministry of Internal Affairs (MIA) of the Republic of Uzbekistan. The author examines in detail systemic, pedagogical, and infrastructural barriers in the process of digital transformation. Special attention is paid to issues of poor internet connectivity, the shortage of specialized electronic resources, and the digital literacy levels of both instructors and trainees. The study concludes with scientific and pedagogical recommendations for the effective organization of the educational process and the realization of the potential of technological innovations.